Case report: Senescence as mechanism of resistance to Pembrolizumab in a Lymphoma patient who failed CD19-Targeted CAR-T cell therapy - De Matteis, Serena; Casadei, Beatrice; Lolli, Ginevra; Dicataldo, Michele; Barbato, Francesco; Dan, Elisa; Paccagnella, Andrea; Sinigaglia, Barbara; Bertuzzi, Clara; Arcari, Annalisa; Zazzeroni, Luca; Bernuzzi, Patrizia; et al. (Frontiers in Immunology, 2022)
Background. T cells engineered to target CD19 antigen on neoplastic B cells represent the most striking example of CAR T-cell therapy. The success rate of this therapy is affected by several limitations, though, including target antigen loss due to tumor evolution and clonal selection and/or acquisition of a senescent and/or exhausted phenotype by CAR expressing T cells. Case presentation. We report on a patient affected by refractory Diffuse Large B-cell Lymphoma who was resistant to CAR T-cell therapy and then, to two cycles of anti-PD-1 pembrolizumab (PBZ) used for the evolution into a B-cell Hodgkin-like lymphoma. Due to the CD30 expression and the Hodgkin-like phenotype, the patient was treated by Brentuximab-Vedotin and finally underwent remission. Conclusions. Our data support the idea that the acquisition of a senescent and exhausted phenotype by CAR+ and non-CAR-expressing cells contributed to the lack of efficacy of PBZ in re-expansion of a functional CAR population. Moreover, our findings underpin the urgent clinical need to search for innovative therapeutic strategies to support the function of CAR T-cells over time, in order to restrain the phenomenon of exhaustion and cell senescence.